Education, Social Mobility, And Empowerment - Namadev H. Bhajantri (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Education is a pivotal factor in promoting social mobility and empowerment, enabling individuals to transcend socio-economic barriers and unlock their potential. This concept explores the interplay between education, social mobility, and empowerment, highlighting the ways in which quality education can foster economic growth, social inclusion, and individual agency. By examining the complex relationships between education, social mobility, and empowerment, this concept aims to inform strategies for promoting equitable access to education and opportunities for all, ultimately contributing to a more just and prosperous society.